The Effect of Picture Word Inductive Model (PWIM) on Students’ Vocabulary Mastery - Kamarudin Kamarudin (Universitas Pendidikan Mandalika, 2021)
This research is aimed at finding out whether using Picture Word Inductive Model has positive effect on students’ vocabulary mastery or not. The research was pre-experimental with pre-test post-test design. The population and sample of the study was second grade students of MTs NW Lingsar which consisted of one class (26 students). The instrument that was used objective test (20 items). The score was analyzed by used descriptive and inferential analysis. Descriptive analysis was used to describe mean; mode, median, and standard deviation of group, and inferential analysis was used to describe the value of t-test for comparison between t-table. It was showed that the value of-test = 4.708 was higher than the value of t-table = 1.708. So, using Picture Word Inductive Model has positive effect on students’ vocabulary mastery at MTs NW Lingsar.